THE EFFECT OF STEERING BLADE ANGLES OF HELICAL TURBINE FOR POWER GENERATION IN IRIGATION DAM OF - Riman Sipahutar; Niharman Niharman (Universitas Sriwijaya, 2015)
The Gorlov vertical axis water turbine is suitable to harness the water flow in the creation of kinetic energy for the irigation dam. The turbine tested in this study was ther Gorlov helical turbine blade with steering angles of 00, 300, 450 and 600 turbine diameter (d) of 0.30 m, height (h) of 0.50 m and the NACA 0020 profile. The testing was conducted on the irigation dam of Seluma Bengkulu. The water flow showed in the velocity (Uair) of Â 0.85 m / s and a round (n) of 110 rpm. The results were achieved by setting the blades in steering torque coefficient (Ct) of 0.309 are turbine efficiency (Î·t) of 28.5% and a power turbine (Pt) of 13.699 Watts.